2015
DOI: 10.1088/2053-1591/2/10/105012
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature homogenization in nanocrystalline PdCu thin film system

Abstract: AbstactDiffusion and solid state reactions were investigated in Pd-Cu nanocrystalline films by means of secondary neutral mass spectrometry depth profiling technique. The heat treatments were made at low temperatures (where the volume diffusion was frozen in) for long enough annealing times to reach saturation. In the early stage there is a grain boundary interdiffusion. At longer times first a Pd plateau developed inside the Cu layer. Later on the Cu penetration was also more and more extended in the Pd, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In addition, in the literature mainly the alloying in the slower component (in B) was investigated and only few results on alloying on the other (faster) side can be found [12,13]. In a more recent series of experimental investigations in our laboratory [14][15][16][17][18][19][20] it was indicated that the compositions in the DIGM zones can be determined by secondary neutral mass spectrometry (SNMS) depth profiling. It was shown that i) as it was illustrated in the Cu/Ni system already in 1983 [21], alloying can also take place in the faster component, similarly as in the slower one of the Ag/Au system [16] and ii) if the grain size is less than half of the average sweeping distance of the GBs, L, a full homogenization is possible, with a saturation at compositions determined by the concentrations left behind the sweeping boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the literature mainly the alloying in the slower component (in B) was investigated and only few results on alloying on the other (faster) side can be found [12,13]. In a more recent series of experimental investigations in our laboratory [14][15][16][17][18][19][20] it was indicated that the compositions in the DIGM zones can be determined by secondary neutral mass spectrometry (SNMS) depth profiling. It was shown that i) as it was illustrated in the Cu/Ni system already in 1983 [21], alloying can also take place in the faster component, similarly as in the slower one of the Ag/Au system [16] and ii) if the grain size is less than half of the average sweeping distance of the GBs, L, a full homogenization is possible, with a saturation at compositions determined by the concentrations left behind the sweeping boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get clear conclusions about the validity of above predictions it is plausible to make a distinction between systems forming solid solutions and systems forming compound. In the latter cases the DIGM drives the system to phase equilibrium, dictated by the bulk phase diagram [19,20], and the description of these systems should go beyond, e.g., the theoretical model of [4], providing the relations in Equation 1 or Equation 2. On the other hand in systems forming solid solutions, according to Equation 1 and Equation 2, the saturation values should be different on the two sides of the couple, predicting a higher value in the slower component (in B).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the literature mainly the alloying in the slower component (in B) was investigated and only few results on alloying on the other (faster) side can be found [ 12 13 ]. In a more recent series of experimental investigations in our laboratory [ 14 20 ] it was indicated that the compositions in the DIGM zones can be determined by secondary neutral mass spectrometry (SNMS) depth profiling. It was shown that i) as it was illustrated in the Cu/Ni system already in 1983 [ 21 ], alloying can also take place in the faster component, similarly as in the slower one of the Ag/Au system [ 16 ] and ii) if the grain size is less than half of the average sweeping distance of the GBs, L , a full homogenization is possible, with a saturation at compositions determined by the concentrations left behind the sweeping boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get clear conclusions about the validity of above predictions it is plausible to make a distinction between systems forming solid solutions and systems forming compound. In the latter cases the DIGM drives the system to phase equilibrium, dictated by the bulk phase diagram [ 19 20 ], and the description of these systems should go beyond, e.g., the theoretical model of [ 4 ], providing the relations in Eq. 1 or Eq.…”
Section: Introductionmentioning
confidence: 99%